PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KARAKTER DALAM PEMBELAJARAN EKONOMI DI SMA NEGERI 1 SUNGAI RAYA - Citra, Iid Elma; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is motivated by an abstract learning system, the explanation still uses words that require students to really understand the subject of study without using interesting learning media so that students are less enthusiastic in learning, as well as in the teaching materials used by educators. not all have character payloads. This study aims to produce learning media in the form of Character Student Worksheets (LKPD) so that students are enthusiastic in the learning process. The research procedure uses the ADDIE development model (Robert Maribe Brach) and the Borg and Gall method, namely analysis, research dan initial information collection, product planning or design, initial testing, and product revision. Data collection techniques are qualitative in the form of revisions by media experts, material experts and learning practitioners, and quantitative data from assessment questionnaires. The results of this study are (1) the assessment of media experts obtained 4.9 and from material experts score obtained was 4.5 from the range of 4.3 to 5 using the MV calculation which is declared very valid or feasible to use. (2) The assessment from the first learning practitioner score was 4.35 and from the second learning practitioner obtained score was 4.2 from the range of 3.5 to 4.2 using the MV calculation which was declared valid or feasible to use. (3) The assessment of all students obtained score was 4.53 from the range of 4.3 to 5 using the MV calculation is declared very valid or feasible to use.